A new long‐tailed basal bird from the Lower Cretaceous of north‐eastern China. (November 2014) - Lefèvre, Ulysse; Hu, Dongyu; Escuillié, François; Dyke, Gareth; Godefroit, Pascal
<x xml:space="preserve">Abstract</x> A new basal Avialae, Jeholornis curvipes sp. nov., from the Yixian Formation (Lower Cretaceous) of Liaoning Province (north‐eastern China) is described. A revision of long‐tailed birds from China and a phylogenetic analysis of basal Avialae suggest that Jeholornithiformes were paraphyletic, with Jixiangornis orientalis being the sister‐taxon of pygostylia. The phylogenetic analysis also recovered that the tail reduction is a unique event in the evolution of birds. Jeholornis species were cursorial, nonperching, and seed‐eating birds. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2014, 113, 790–804.